ANALISIS PROSEDUR AKUNTANSI DALAM PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) PADA SMA NEGERI 1 WUNDULAKO - Juniati, Juniati; Triani, Neks; Sabarudin, Sabarudin (Jurnal Akuntansi Kompetif, 2025)
This study aims to describe the accounting procedures used in the management of School Operational Assistance (BOS) funds at SMA Negeri 1 Wundulako. The problem formulations in this study are: 1) What are the accounting procedures for managing School Operational Assistance (BOS) funds at SMA Negeri 1 Wundulako? 2) Does the accounting system for managing School Operational Assistance (BOS) funds at SMA Negeri 1 Wundulako comply with the National Education Standards and BOS Technical Guidelines? This research uses qualitative analysis with a case study approach. Data collection involved observation, documentation, and interviews with research subjects. Validity tests were conducted using source triangulation, technical triangulation, and time triangulation. Data analysis techniques included data reduction, data presentation, and data verification. The results of the study indicate: 1) the management of BOS funds at SMA Negeri 1 Wundulako is in accordance with the 2022 BOS technical guidelines. BOS fund management has three important aspects, namely planning, implementation, and reporting. In the management of BOS at SMA Negeri 1 Wundulako, there are several shortcomings, namely in the process of preparing the RKAS where there is no budget allocated to finance the development of graduate compensation standards; development of content standards; and development of educators and education personnel. Furthermore, there are obstacles in the process of distributing BOS funds which are often delayed so that the school must go into debt to resolve the problem. Another problem is that at any time the school suddenly requires carrying out an activity whose implementation budget is not listed in the RKAS. The solution that the school can do to overcome this problem is to go into debt; 2) the use of BOS funds at SMA Negeri 1 Wundulako has been maximized to meet the needs of the school. However, maximizing the use of BOS funds so that it can reach all components in the school. Accounting Procedures, Management, BOS Funds